DRAMA MASTERSHIP PEDAGOGUES ACTVITIES’ HISTORICAL DEVELOPMENT AT THE THEATRES OF LATVIA - Strads, Gatis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article gives an insight into the theatre department pedagogue activity for the training of the emerging drama actors for practice at theatre at Arts higher education school. Monographs, scientific publication materials and archive documents have been analysed on pedagogues’ activities at the theatre faculty and the former and the existing pedagogues’ interview data about the student training for activity at theatre. The comparative analysis of the drama art study programmes from 1948 till 2015 has been accomplished. The fact has been emphasized that different directors through times base Latvian drama art on K. Stanislavsky’s notions of the drama mastery of actors due to the successive professional activity implementation at the theatre. The conclusion has been drawn that the emerging actors’ personalities are significant in the training of the emerging actors, their human development would be promoted by inclusion of pedagogy and psychology subjects in the studies by the emerging actors at the tertiary level.